DEVELOPMENT OF CIPROFLOXACIN LOADED THROAT PAINT FOR THE TREATMENT OF STREP THROAT INFECTION - KUMAR SINGH, RAHUL; SUNAINA, KUMARI; KUMAR DUBEY, AMIT; YADAV, NARENDRA (Asian Journal of Pharmaceutical and Clinical Research, 2022)
Objective: This study is to enhance the solubility and sustained release of ciprofloxacin (CPX) drug by amplifying the adhesive capability of formulation by forming throat paint for the Streptococcal pharyngitis, a sore throat infection. Methods: Solid dispersion was prepared by solvent evaporation technique, in which three different ratios of Polyethylene glycol-6000 (PEG-6000) were selected, and the best ratio of solid dispersion was selected after characterization including Scanning electron microscopy (SEM) and Differential scanning calorimetry (DSC) with evaluation parameters including % yield, drug content, and drug solubility. In the case of throat paint, out of six different formulations, the best formulation was selected through viscosity, in vitro mucoadhesion, in situ release study, and spreadability parameters. Results: The DSC and SEM data proved that solid dispersion has a different moiety than its ingredients but it is quite a stable form. Formulation MD-2 was selected as the best formulation which able to increase the solubility of the drug by more than 3.5 folds, at the same time it shows the highest rate of drug dissolution of 13.951 μg/ml with % yield (97.199±0.167%) and drug content (96.425%). Throat paint was formed by fusion and trituration process and out of all six formulations F3 was selected as the best formulation on the basis of Viscosity (11932 Centi poise), Spreadability (17.621), Mucoadhesion (3937.481 dyne/cm2), and drug release (90.336±0.6%). Conclusion: Solid dispersion was successfully prepared with 3.5 times of solubility enhancement capability in comparison with pure CPX drug. The throat paint releases the drug (≥3 h) in a sustained manner with high mucoadhesive force.